Clinical characteristics and risk factors of chronic critical illness in children with sepsis - Yang, Lin; Zang, Na; Liu, Cong; Yang, Ying; Pu, Kai Bing; Tan, Li Ping; Liu, En Mei (Frontiers in Pediatrics, 2025)
ObjectivesThis study aimed to examine the clinical characteristics and risk factors associated with the development of chronic critical illness (CCI) in children with sepsis.MethodsA retrospective analysis was conducted on children diagnosed with sepsis and admitted to the Pediatric Intensive Care Unit (PICU) at Chongqing Medical University Affiliated Children's Hospital between January 2015 and December 2022. Patients were categorized into two groups based on clinical outcomes: CCI group, defined by an ICU stay ≥14 days with persistent organ dysfunction, and non-CCI group, including patients with rapid recovery or early death. Data on baseline demographics, clinical characteristics, and diagnostic and therapeutic differences were collected and analyzed.ResultsAmong 1,326 children with sepsis, 244 were classified in the CCI group (135 males, 109 females) and 1,082 were classified in the non-CCI group (651 males, 431 females), including 163 cases in the early death group and 919 cases in the rapid recovery group. No significant differences were observed between the groups in terms of sex, age distribution, or prevalence of septic shock. Respiratory and gastrointestinal infections were the predominant sources of infection in both groups. Compared to the non-CCI group, the CCI group exhibited significantly higher weights, pediatric sequential organ failure assessment (pSOFA) scores, rates of underlying respiratory diseases, trauma, surgical interventions, mechanical ventilation duration, ICU stay, total hospital stay, and secondary infection rates. Multivariate logistic regression identified pSOFA score, underlying respiratory diseases, trauma, prolonged mechanical ventilation, surgical interventions, and secondary infections as independent risk factors for the development of CCI in children with sepsis. Based on ROC analysis, the AUC of the established CCI prediction model was 0.902 (95% CI: 0.873–0.928). Secondary infections were also a prominent clinical feature of CCI cases.ConclusionsCCI in pediatric sepsis is associated with underlying respiratory diseases, trauma, elevated pSOFA scores, surgical procedures, prolonged mechanical ventilation and secondary infections. These factors contribute to extended hospital stays, elevated secondary infection rates, and poor clinical outcomes. The persistence of pro-inflammatory mediators and subsequent immunosuppression may underlie the development of CCI in this population.